COMMUNITY PERCEPTION OF CHICKEN LAYER FARMING IN JAJAR HAMLET, KANIGORO VILLAGE, KANIGORO DISTRICT, BLITAR DISTRICT - Widianto Aji Lusiyo; Alfan Setya Winurda; Edya Moelia Moeis (Journal of Livestock Science and Production, 2024)
This research aims to understand the influence of the community in Jajar halmet, Kanigoro village, Kanigoro sub-district, Blitar district form 11 July to July 18, 2024.. The research used Google form and distribute questionnaires to 43 respondens online. The obseved variabel pollution air , pollution water , influence on land, and social environment. Respondent characteristics observed included  age, and educational level. The result of the research show are dominated by the age of 20-30 with a total of  20 (48%). Respondent viewed by the level education, mostly have an educational background of SMA/SMK  21 (49%). Respondents’ perceptions of livestock in Jajar Hamlet are: water pollution 28 (quite disturbed) ; air pollution 59 (moderately disturbed) ; fly 57 (very disturbed); influence on soil 32 (undisturbed).mjl,